A Prototype Exercise–Empowerment Mobile Video Game for Children With Cancer, and Its Usability Assessment: Developing Digital Empowerment Interventions for Pediatric Diseases - Bruggers, Carol S.; Baranowski, Sabrina; Beseris, Mathew; Leonard, Rachel; Long, Derek; Schulte, Elizabeth; Shorter, Ashton; Stigner, Rowan; Mason, Clinton C.; Bedrov, Alisa; Pascual, Ian; Bulaj, Grzegorz (Frontiers in Pediatrics, 2018)
Background: Medical advances continue to improve morbidity and mortality of serious pediatric diseases, including cancer, driving research addressing diminished physical and psychological quality of life in children with these chronic conditions. Empowerment enhances resilience and positively influences health, disease and therapy understanding. We describe the development and usability assessment of a prototype Empower Stars! mobile video game, grounded in behavioral and exercise theories, with the purpose of coupling physical exercise with empowerment over disease in children with cancer. Methods: Academic faculty, healthcare providers and community video game developers collaborated in this project. The iPadAir was selected as a delivery platform for its accelerometer and gyroscope features facilitating exercise design. Unity multiplatform technology provided animation and audiovisual features for immediate player feedback. Javascript, C#, Photoshop, Flash, and SketchUp were used for coding, creating graphical assets, Sprite sheets, and printing files, respectively. 3D-printed handles and case-backing were used to adapt the iPad for physical exercise. Game usability, engagement, and enjoyment were assessed via a multi-level study of children undergoing cancer chemotherapy, their parents, and pediatric cancer healthcare providers. Feedback crucial for ongoing game development was analyzed. Results: A prototype Empower Stars! mobile video game was developed for children 7-14 years old with cancer. Active, sedentary, educational and empowerment-centered elements intermix for 20 minutes of exercise within a 30 minute “one-day treatment” gameplay session involving super-heroes, space exploration, metaphorical cancer challenges, life restoration on a barren planet and innumerable star rewards. No player “dies.” Usability assessment data analyses showed widespread enthusiasm for integrating exercise with empowerment over cancer and for the game itself. Favorite elements included collecting star rewards and planet terraforming. Traveling in space and the Healthy Food Choice game were least liked. The need for improved gameplay instructions was expressed by all groups. The usability study provided essential feedback for converting the prototype into alpha version of Empower Stars! Conclusions: Adapting exercise empowerment-promoting video game technology to mobile platforms facilitates usability and widespread dissemination for children with cancer. We discuss broader therapeutic applicability in diverse chronic pediatric diseases, including obesity, asthma, cystic fibrosis, diabetes and juvenile idiopathic arthritis.